Mathematical competences in bovine production - Chávarro Murcia, Cristian Javier
The contextualization of mathematical knowledge for problem-solving in real life is a didactic strategy that strengthens competencies within the framework of Integral Professional Training. In this sense, the characterization of the Bovine Productive Unit of the Agroindustrial Training Center was undertaken with apprentices of the Livestock Production Technologist, to learn in context the concepts related to geometric bodies. The process showed an improvement in the knowledge of the trainees as well as an active participation, although the basic mathematical knowledge should be further reinforced.